Effects of TiO2 addition and electron irradiation on superconducting and mechanical properties of Bi2Sr 2CaCu2O8 (Bi-2212) superconductor - Hamid N.A.; Abdullah Y.; Abdullah M.H.P. (American Institute of Physics Inc., 2023)
Titanium Oxide (TiO2) compounds having very high melting point with lower heat capacity, is an excellent candidate for reinforcement of brittle materials such as superconductor ceramics. In addition to high melting point, the TiO2 is also capable of establishing flux pinning centers in bismuth-based superconductors such as the Bi-2212. To further enhance the flux pinning properties, irradiation is one of the techniques that can be used to re-create the required point defects. In this study, the effects of TiO 2 addition and electron irradiation on Bi-2212 superconductor were studied. TiO2 added Bi-2212 superconductor samples with 5%, 10% and 15% weight percentage addition respectively, were prepared using the conventional solid-state reaction method. The samples were irradiated with electron beam with radiation dose of 100 KGray. Characterization was performed by X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The transition temperature (Tc) and the critical current density (J c) of the samples were also measured. The XRD patterns for all the samples show well-defined peaks all of which could be indexed on the basis of a Bi-2212 phase structure. In addition, the XRD patterns indicate that electron irradiation did not change the structure of Bi-2212 superconducting phase. Results of SEM micrographs show disorientation in the texture of the microstructure for samples that are subjected to electron irradiation. The grains are seen to align randomly with higher degree of orientation. With regard to TiO2 additions, only small TiO2 addition sustained the superconducting properties upon irradiation. Addition of more than 5% weight percentage of TiO2 degrades the superconducting properties of the irradiated samples. Formation of weak-links may result in higher grain boundaries orientation within the superconducting grains and thus deteriorates the inter-grains connectivity and resulted in lower Tc and degradation of Jc. The strength of the superconductor reduced significantly when subjected to electron irradiation. © 2014 AIP Publishing LLC.